FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKS PRANIKAH PADA REMAJA DI SMA NEGERI 7 KABUPATEN BENGKULU SELATAN - Violita Siska Mutiara; Iwan Suryadi; Faula Ningsih (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2017)
Adolescent is a transition period or transition from childhood to adulthood marked by physical, psychological and psychosocial changes. The type of this study used method of Analytic Survey with Cross Sectional design was to determine relationship between risk factors with effects, by way of approach, observation or data collection at once at a time or at the same time Data collection in this studyused primary data by looking at distributing questionnaires to students who were sampled. Data analysis was done by univariate and bivariate analysis. The results of this study were: 34 respondents (49.3%) of respondents had bad pre-marital sex behavior, 39 respondents (56.5%) of respondents had less knowledge, 47 respondents (68.1%) had unfovaroble attitude, 43 respondents (62,3%) of respondents have an unfavorable environment, there was a relationship between adolescent knowledge withpre-marriage sexual behavior (strong category, there was a relationship between adolescent attitudes with pre-marriage sex behavior (medium category). and there was relationship between adolescent environment with pre-marriage sex behavior in SMAN 7 South Bengkulu Regency. The results of this study were expected to provide an overview of factors that affect pre-marriage sex behavior in adolescents in high school. Keywords : Attitude, environment, knowledge, pre-marriage sex behavior